Altering retinol binding protein 4 levels in hepatitis C: Inflammation and steatosis matter - Ming-Ling Chang (Taylor & Francis Group, 2020)
Both hepatitis C virus (HCV) infection and retinol-binding protein 4 (RBP4) might contribute to insulin resistance (IR), how RBP4 links to IR in HCV infection remain elusive. A joint study of a prospective cohort of 842 chronically HCV-infected (CHC) patients (with 842 controls) and a line of HCV core transgenic mice was conducted. Of 842 patients, 771 had completed anti-HCV therapy and 667 had sustained virological responses (SVRs). Compared with controls, CHC patients had lower RBP4 levels. At baseline, age (95% CI β: −0.87~−0.317), BMI (0.516~2.036), triglycerides (0.03~0.127), neutrophil-to-lymphocyte ratio (NLR) (1.561~7.327), and estimated glomerular filtration rate (eGFR) (−0.342~−0.149) levels were associated with RBP4 levels in CHC patients. At 24-week post-therapy, male sex (0.652~8.129), BMI (0.199~1.254), triglycerides (0.039~0.088), uric acid (0.599~3.067), eGFR (−0.247 ~−0.14) levels, and fibrosis-4 (−3.602~−0.039) scores were associated with RBP4 levels in SVR patients; compared with baseline, except genotype 3 HCV-infected patients, SVR patients had increased RBP4 levels, which were comparable with controls, while no HOMA-IR index alteration was noted after SVR. The HCV core transgenic mice exhibited nonobese hepatic steatosis, had higher hepatic RBP4 expression, higher serum levels of RBP4 and triglycerides, but comparable HOMA-IR levels than non-transgenic littermates. In conclusion, steatosis, sex, age, uric acid, NLR, and FIB-4 levels were associated with HCV-related RBP4 levels; BMI, triglycerides, and eGFR levels were associated with non-HCV-related RBP4 levels. Reversal of low RBP4 levels after SVR was evident in non-genotype 3 HCV-infected patients. Steatosis and inflammation linked with metabolic alteration other than IR, determined RBP4 levels in HCV-infected patients.